2009
DOI: 10.1111/j.1365-2915.2009.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the bionomics of Phlebotomus sergenti sandflies from an endemic area of anthroponotic cutaneous leishmaniasis in Aleppo Governorate, Syria

Abstract: Aspects of the bionomics of phlebotomine sandflies (Diptera: Psychodidae) were studied from June to November 2005 in three foci of anthroponotic cutaneous leishmaniasis (ACL) in Aleppo Governorate, Syria, where the agent Leishmania tropica (Wright) (Kinetoplastida: Trypanosomatidae) is transmitted by Phlebotomus sergenti Parrot. Syria has been designated by the World Health Organization as one of four countries in the Old World where cutaneous leishmaniasis is hyperendemic, but little is known about the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…Several studies have demonstrated that cats constitute sources of blood for sand flies (Johnson et al, 1993;Ogusuku et al, 1994;Maroli et al, 2009;Afonso et al, J HELLENIC VET MED SOC 2017, 68(1) ΠΕΚΕ 2017 2012; Baum et al, 2013). ΀he ability of the vector to properly complete feeding on cats and acquire infection has been indirectly proved after the experimental demonstration of infectiousness of two infected cats to sand flies (Maroli et al, 2007;da Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that cats constitute sources of blood for sand flies (Johnson et al, 1993;Ogusuku et al, 1994;Maroli et al, 2009;Afonso et al, J HELLENIC VET MED SOC 2017, 68(1) ΠΕΚΕ 2017 2012; Baum et al, 2013). ΀he ability of the vector to properly complete feeding on cats and acquire infection has been indirectly proved after the experimental demonstration of infectiousness of two infected cats to sand flies (Maroli et al, 2007;da Silva et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of the ITS1 gene amplified from skin lesions of 70 patients showed that L. tropica is the causative agent of CL in both provinces. This species is also the main agent of CL in the highly endemic Aleppo province, northern Syria [ 9 , 36 ] and in several foci in neighbouring countries [ 37 , 38 ]. PCR-RFLP analysis of the ITS1 gene is commonly used to detect intraspecific genetic diversity among L. tropica species [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…They added that the widespread co-distribution of M. guentheri and P. papatasi, suggested a significant threat from the spread of ZCL in the Middle East, central Asia and southern Europe. Maroli et al (2009) in Syria identified three foci of anthroponotic cutaneous leishmaniasis (ACL) in Aleppo Governorate. The common sandflies were P. papatasi (68%); P. sergenti (25.4%); Sergentomyia minuta (6.4%); P. tobbi (0.1%), and P. mascittii canaaniticus (0.1%).…”
Section: Review and Discussionmentioning
confidence: 99%